Difficulties of Prenatal Genetic Counseling for a Subsequent Child in a Family With Multiple Genetic Variations - Huang, Ting-Xuan; Ma, Gwo-Chin; Chen, Ming; Li, Wen-Fang; Shaw, Steven W. (Frontiers in Genetics, 2021)
Many parents with a child with disabilities appreciate the option of prenatal genetic diagnosis to understand the chance of recurrence of the genetic condition in a future pregnancy. Genome-wide tests, such as chromosomal microarray analysis and whole exome sequencing, have been increasingly used for prenatal diagnosis but prenatal counseling can be challenging due to the complexity of genomic data. The situation is further complicated by incidental findings of additional genetic variations in subsequent pregnancies. Here, we report the prenatal identification of a baby with a MECP2 missense mutation and 15q11.2 microduplication in a family that has had a child with developmental epileptic encephalopathy caused by a de novo KCNQ2 mutation. An extended segregation analysis including more relatives, in addition to the parents, was carried out to provide further information for genetic counseling. This case illustrates challenges of prenatal counseling and highlights the need of understanding of clinical and ethical implications of genome-wide tests.